2016
DOI: 10.2174/1389450116666151102095046
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Monophosphate-activated Protein Kinase (AMPK) Activators For the Prevention, Treatment and Potential Reversal of Pathological Pain

Abstract: Pathological pain is an enormous medical problem that places a significant burden on patients and can result from an injury that has long since healed or be due to an unidentifiable cause. Although treatments exist, they often either lack efficacy or have intolerable side effects. More importantly, they do not reverse the changes in the nervous system mediating pathological pain, and thus symptoms often return when therapies are discontinued. Consequently, novel therapies are urgently needed that have both imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 159 publications
1
50
0
Order By: Relevance
“…Our in vitro experiments on DRG neurons indicate the combination of resveratrol and metformin activate AMPK in at least an additive fashion. These data add to a growing body of evidence that AMPK activation can inhibit the development of acute mechanical hypersensitivity resulting from injury (Melemedjian et al, 2011, Tillu et al, 2012a, Russe et al, 2013, Bullon et al, 2015, Ma et al, 2015, Song et al, 2015, Maixner et al, 2016, Ling et al, 2017), reduce the excitability of nociceptors (Melemedjian et al, 2011, Tillu et al, 2012a, Melemedjian et al, 2013, Asiedu et al, 2017) and prevent the development of hyperalgesic priming (Price and Dussor, 2013, Price et al, 2015, Asiedu et al, 2016, Mejia et al, 2016). We conclude that topical resveratrol and co-treatment of various AMPK activators such as metformin are clinically relevant and could show utility as pain therapeutics in humans.…”
Section: Discussionmentioning
confidence: 58%
“…Our in vitro experiments on DRG neurons indicate the combination of resveratrol and metformin activate AMPK in at least an additive fashion. These data add to a growing body of evidence that AMPK activation can inhibit the development of acute mechanical hypersensitivity resulting from injury (Melemedjian et al, 2011, Tillu et al, 2012a, Russe et al, 2013, Bullon et al, 2015, Ma et al, 2015, Song et al, 2015, Maixner et al, 2016, Ling et al, 2017), reduce the excitability of nociceptors (Melemedjian et al, 2011, Tillu et al, 2012a, Melemedjian et al, 2013, Asiedu et al, 2017) and prevent the development of hyperalgesic priming (Price and Dussor, 2013, Price et al, 2015, Asiedu et al, 2016, Mejia et al, 2016). We conclude that topical resveratrol and co-treatment of various AMPK activators such as metformin are clinically relevant and could show utility as pain therapeutics in humans.…”
Section: Discussionmentioning
confidence: 58%
“…Recent preclinical studies have suggested that metformin, a drug approved by the US Food and Drug Administration (FDA) for glycemic control in patients with type 2 diabetes, alleviates neuropathic and inflammatory pain in various models . We demonstrated that metformin also prevents cisplatin‐induced neuropathic pain, numbness, and loss of IENFs .…”
Section: Introductionmentioning
confidence: 81%
“…Indeed, there are indications that these agents may mediate their effects through other cellular signaling pathways including those that involve pro-inflammatory cytokines, protein kinases, growth factors, and reactive oxygen species (ROS). 15,73,121,142,143 …”
Section: Second Messenger Pathwaysmentioning
confidence: 99%